IMPLEMENTASI NILAI-NILAI ISLAM DALAM PEMBELAJARAN DI SDN 006 MELAYU BESAR: PENDEKATAN KUALITATIF DESKRIPTIF - Rambe, Syahro (Al Ghazali, 2024)
This research aims to examine the implementation of Islamic values in learning at SDN 006 Melayu Besar. The main focus of this research is to understand how these values are applied in the teaching and learning process and the challenges faced by teachers. This research uses a descriptive qualitative approach, where data is collected through direct observation, in-depth interviews with teachers and students, and documentation analysis. The research results show that the implementation of Islamic values is carried out through integration in subjects, extracurricular activities and daily habits. Teachers act as the main role models in implementing these values, and they use various methods, such as group discussions and inspirational stories. However, several challenges were identified, including time constraints and lack of support from parents. However, support from schools and collaboration between teachers helped overcome these obstacles. It can be seen that the implementation of Islamic values at SDN 006 Melayu Besar is quite effective, although there needs to be an increase in teacher training and parent involvement.